The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/art.37970
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral Bone Trabecular Integrity Predicts and Changes Concurrently With Radiographic and Magnetic Resonance Imaging–Determined Knee Osteoarthritis Progression

Abstract: Objective To evaluate subchondral bone trabecular integrity (BTI) from a radiograph as a predictor of knee osteoarthritis (OA) progression. Methods Longitudinal (baseline, 12- and 24-month) knee radiographs were available from 60 female subjects with knee OA. OA progression was defined by 12- and 24-month change in radiographic medial compartment minimal joint space width (JSW) and medial joint space area (JSA), and medial tibial and femoral cartilage volume from magnetic resonance imaging. Bone Trabecular I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 51 publications
6
59
0
Order By: Relevance
“…OA bone's hardness is 7% lower than that of osteoporotic bone, indicating that OA bone has a reduced elastic modulus 29 . These results support the view of a more generalized bone metabolic disease in OA [30][31][32] and that alteration of subchondral bone integrity is a key event in OA 33 .…”
Section: Discussionsupporting
confidence: 87%
“…OA bone's hardness is 7% lower than that of osteoporotic bone, indicating that OA bone has a reduced elastic modulus 29 . These results support the view of a more generalized bone metabolic disease in OA [30][31][32] and that alteration of subchondral bone integrity is a key event in OA 33 .…”
Section: Discussionsupporting
confidence: 87%
“…Radiographic indices of subchondral bone integrity have previously been associated with increased cartilage thickness[10] and decreased risk of progressive joint space loss [9]. Previous MR studies have demonstrated alterations in microstructural trabecular morphometry measurements between volunteers and individuals with OA [13,14], and that such measurements correlate well with severity of OA [15].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, biomarkers of early changes in SB architecture may be helpful in the early detection and monitoring of OA as well as evaluation of treatment response. SB architecture has been evaluated using radiography, employing techniques such as fractal signature analysis [8,9], bone density measurement [10] and trabecular microstructural analysis [11]. Such techniques have had some success in demonstrating associations between changes in SB structure/density with onset and progression of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Kraus et al [31] have shown that bone trabecular integrity assessed by fractal signature on plain knee radiographs could predict structural progression over 24 months as determined by radiographic and MRI outcomes. Altogether, these clinical studies support strong evidence that subchondral bone is a key factor in the onset and the progression of the disease.…”
Section: Key Pointsmentioning
confidence: 98%